The devil is disorder : bodies, spirits and misfortune in a Trinidadian village - Lynch, Rebecca (Research fellow) (Berghahn, 2020)
"What role might the Devil have in health and illness? The Devil is Disorder explores constructions of the body, health, illness and wider misfortune in a Trinidadian village where evangelical Christianity is growing in popularity. Based on long-term ethnography and locating the village in historical and global context, the book takes a nuanced cosmological approach to situate evangelical Christian understandings as shaping and being shaped by their context and, in the process, shaping individuals themselves. As people move from local to global subjects, health here stretches beyond being a matter of individual bodies and is connected to worldwide flows and networks, spirit entities, and expansive moral orders"--